Production of genetically engineered mice with higher efficiency, lower mosaicism, and multiplexing capability using maternally expressed Cas9 - Sakurai, Takayuki (Sci Rep, 2020)
The CRISPR/Cas9 system is widely used to generate gene-edited animals. Here, we developed an efficient system for generating genetically modified mice using maternal Cas9 from Cas9 transgenic mice. Using this system, we achieved lower mosaicism and higher rates of knock-in success, gene-editing, and birth compared to the similar parameters obtained using exogenously administered Cas9 (mRNA/protein) system. Furthermore, we successfully induced simultaneous mutations at multiple loci (a maximum of nine). Our novel gene-editing system based on maternal Cas9 could potentially facilitate the generation of mice with single and multiple gene modifications.